2021
DOI: 10.1111/ocr.12476
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intraoral non‐pharmacological non‐surgical adjunctive interventions on orthodontically induced inflammatory root resorption in humans: A systematic review

Abstract: Background The current systematic review aimed to assess the impact of intraoral non‐surgical non‐pharmacological adjunctive interventions on orthodontically induced inflammatory root resorption (OIIRR). Search methods Search without restrictions was performed up to November 2020 in three electronic databases (Cochrane Central Register of Controlled Trials, MEDLINE and EMBASE) for randomized controlled trials (RCTs), prospective and retrospective non‐randomized studies. The ROB 2.0 tool was used to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…Evidence-based medical research has also shown that high-frequency vibrations can accelerate orthodontic tooth movement by promoting the differentiation of osteoblasts, fibroblasts, and osteoclasts and increasing bone remodeling; thereby accelerating the process [ 55 , 56 ]. In addition, high-frequency vibrations can reduce the risk of root resorption after orthodontic treatment [ 57 ]. The research included in this study involved the use of Accelent and Vpro5 vibrators.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based medical research has also shown that high-frequency vibrations can accelerate orthodontic tooth movement by promoting the differentiation of osteoblasts, fibroblasts, and osteoclasts and increasing bone remodeling; thereby accelerating the process [ 55 , 56 ]. In addition, high-frequency vibrations can reduce the risk of root resorption after orthodontic treatment [ 57 ]. The research included in this study involved the use of Accelent and Vpro5 vibrators.…”
Section: Discussionmentioning
confidence: 99%